Управление кредитным риском и пути его минимизации в коммерческом банке - Присяжная, И.А. (Культура народов Причерноморья, 2013)
В статье на основе научных работ отечественных ученых рассмотрены сущность
кредитного риска, виды рисков, анализ кредитного портфеля, резервы по просроченной задолженности
украинских банков, были предложены мероприятия для минимизации кредитного риска. Рассмотрены
нормативы, установленные Национальным банком Украины с помощью которых, банк может
управлять кредитным риском, выявлены самые рисковые банки в 2012 году по нормативу НБУ Н8, а
также рассмотрены теоретико-практические аспекты по совершенствованию методов минимизации
кредитного риска. При этом автор рассматривает подходы по внедрению новых эффективных путей
совершенствования минимизации кредитных рисков.
Ключевые слова: кредитный риск, нормативы кредитного риска, методы минимизации кредитного
риска, оценка кредитоспособности заемщика, резервирования. У статті на основі наукових робіт вітчизняних вчених розглянуто сутність кредитного
ризику, види ризиків, аналіз кредитного портфеля, резерви по простроченої заборгованості українських
банків, були запропоновані заходи для мінімізації кредитного ризику. Розглянуті нормативи, встановлені
Національним банком України за допомогою яких, банк може управляти кредитним ризиком, виявлені
ризикові банки в 2012 році за нормативом НБУ Н8, а також розглянуті теоретико-практичні аспекти
щодо вдосконалення методів мінімізації кредитного ризику. При цьому автор розглядає підходи щодо
впровадження нових ефективних шляхів удосконалення мінімізації кредитних ризиків.
Ключові слова: кредитний ризик, нормативи кредитного ризику, методи мінімізації кредитного ризику,
оцінка кредитоспроможності позичальника, резервування. The dynamic processes of development and transformation of modern market environment lead to a
significant increase of competition on the internal and external markets, which, in turn, leads to the emergence
of new and modification of existing risk factors that affect the organization and the effectiveness of the
implementation of banking activities. Naturally, this is accompanied by the actualization of the problem of
improving the efficiency of the management of banking risks.
The banking sector is characterised by a high risky nature compared with other types of activity. This feature is
caused by specificity of functions carried out by each commercial Bank.
In article on the basis of scientific works of scientists examined the essence of the credit risk, the types of risk,
the analysis of the loan portfolio, reserves for bad debts of Ukrainian banks, were proposed measures to
minimise credit risk. Considered the norms established by the National Bank of Ukraine with the help of which
the Bank may manage credit risk, identified the most risky banks in 2012, in compliance with the NBU H8, and
the theoretical and practical aspects of the improvement of the methods of credit risk minimisation. The author
considers the approaches to implementation of new effective ways of improving the minimization of credit risks.
Keywords: credit risk, standards of credit risk, methods of minimization of credit risk, assessment of solvency of
the borrower, reservation.